Socio-demographic factors associated with early antenatal care visits among pregnant women in Malawi: 2004-2016. - Wingston Felix Ng'ambi; Joseph H Collins; Tim Colbourn; Tara Mangal; Andrew Phillips; Fannie Kachale; Joseph Mfutso-Bengo; Paul Revill; Timothy B Hallett (PLoS ONE)
Introduction In 2016, the WHO published recommendations increasing the number of recommended antenatal care (ANC) visits per pregnancy from four to eight. Prior to the implementation of this policy, coverage of four ANC visits has been suboptimal in many low-income settings. In this study we explore socio-demographic factors associated with early initiation of first ANC contact and attending at least four ANC visits ("ANC4+") in Malawi using the Malawi Demographic and Health Survey (MDHS) data collected between 2004 and 2016, prior to the implementation of new recommendations. Methods We combined data from the 2004-5, 2010 and 2015-16 MDHS using Stata version 16. Participants included all women surveyed between the ages of 15-49 who had given birth in the five years preceding the survey. We conducted weighted univariate, bivariate and multivariable logistic regression analysis of the effects of each of the predictor variables on the binary endpoint of the woman attending at least four ANC visits and having the first ANC attendance within or before the four months of pregnancy (ANC4+). To determine whether a factor was included in the model, the likelihood ratio test was used with a statistical significance of P< 0.05 as the threshold. Results We evaluated data collected in surveys in 2004/5, 2010 and 2015/6 from 26386 women who had given birth in the five years before being surveyed. The median gestational age, in months, at the time of presenting for the first ANC visit was 5 (inter quartile range: 4-6). The proportion of women initiating ANC4+ increased from 21.3% in 2004-5 to 38.8% in 2015-16. From multivariate analysis, there was increasing trend in ANC4+ from women aged 20-24 years (adjusted odds ratio (aOR) = 1.27, 95%CI:1.05-1.53, P = 0.01) to women aged 45-49 years (aOR = 1.91, 95%CI:1.18-3.09, P = 0.008) compared to those aged 15-19 years. Women from richest socio-economic position ((aOR = 1.32, 95%CI:1.12-1.58, P<0.001) were more likely to demonstrate ANC4+ than those from low socio-economic position. Additionally, women who had completed secondary (aOR = 1.24, 95%CI:1.02-1.51, P = 0.03) and tertiary (aOR = 2.64, 95%CI:1.65-4.22, P<0.001) education were more likely to report having ANC4+ than those with no formal education. Conversely increasing parity was associated with a reduction in likelihood of ANC4+ with women who had previously delivered 2-3 (aOR = 0.74, 95%CI:0.63-0.86, P<0.001), 4-5 (aOR = 0.65, 95%CI:0.53-0.80, P<0.001) or greater than 6 (aOR = 0.61, 95%CI: 0.47-0.79, <0.001) children being less likely to demonstrate ANC4+. Conclusion The proportion of women reporting ANC4+ and of key ANC interventions in Malawi have increased significantly since 2004. However, we found that most women did not access the recommended number of ANC visits in Malawi, prior to the 2016 WHO policy change which may mean that women are less likely to undertake the 2016 WHO recommendation of 8 contacts per pregnancy. Additionally, our results highlighted significant variation in coverage according to key socio-demographic variables which should be considered when devising national strategies to ensure that all women access the appropriate frequency of ANC visits during their pregnancy.